Differences in the Perception of Sexual Harassment by Gender and Ethnicity among Selected Malaysian Undergraduates - Yee, M.T.W.; Alagappar, P.N.; Ngeow, Y.M. (Taylor & Francis, 2015)
Sexual harassment is generally perceived as a social issue predominantly found in the workplace. However, it can also occur at various stages of youth and adolescence. University students who will soon join the workforce are equally vulnerable to sexual harassment. It is hypothesized that lack of understanding and awareness of what constitutes sexual harassment have made the youth easy targets of perpetrators. This study identifies the level of awareness and perceptions of sexual harassment among students in a public university of Malaysia. Being multiethnic and multicultural, Malaysia offers a diverse social demographic context for comparison across ethnic groups such as the Malay, Chinese, and Indian. This study further explores how gender, ethnicity, culture, and personal encounters shape one’s perceptions of sexual harassment. We hope this empirical study will shed light for stakeholders in youth development to address this critical but under-publicized youth issue. It is also noteworthy that this study does not support the literature that sexual harassment often leads to negative psychosocial effects. Instead, the findings show that prior experiences of sexual harassment actually increase the level of sensitivity in identifying and reacting to incidents of sexual harassment.